Strategi Pengelolaan Risiko Dalam Konstruksi Gedung Tahan Gempa Di Daerah Rawan Bencana - Harita, Hamedoni; Daeli, Serta Denius; Zalukhu, Muhammad Haris; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2024)
The development of earthquake-resistant infrastructure in disaster-prone areas requires a holistic and evidence-based approach to risk management. Indonesia, located in the Pacific Ring of Fire, faces a high earthquake risk, making risk management essential in construction projects. This study explores strategies for mitigating risks in earthquake-resistant building projects by reviewing literature and case studies. Key findings highlight the effectiveness of Building Information Modelling (BIM) and adherence to international standards like Eurocode 8 and ASCE 7-16 in minimizing construction risks. BIM enhances project planning and collaboration, while international standards provide robust guidelines for structural design, reducing earthquake impacts. Challenges, such as limited budgets, technical knowledge gaps, and poor coordination among project stakeholders, were identified. These findings emphasize the need for a comprehensive approach to managing construction risks in earthquake-prone regions. Integrating technology, standards, and risk management practices is crucial to ensure structural integrity and occupant safety in earthquake-resistant buildings.